Job Stress, Job Satisfaction, Self-Efficacy and Turnover Intentions across Socio-Demographic Characteristics of Government Secondary School Teachers in Greater Mbarara - Innocent Nkwatsibwe; Aloysius Rukundo; Sudi Balimuttajjo (American Journal of Education and Practice, 2025)
Purpose: The study examined the levels job stress, job satisfaction, self-efficacy and turnover intentions across socio-demographic characteristics of government secondary school teachers in greater Mbarara. Materials and Methods: The cross-sectional, quantitative study adopted census strategy select schools and simple random sampling to select respondents. Data was collected from 470 teachers using self-administered questionnaires. Data was analyzed using frequencies, means, standard deviations, independent samples t test and one-way ANOVA. Findings: Generally, teachers reported moderate job stress, job satisfaction and turnover intentions while self-efficacy was high. High stress was reported among males (M=2.962), teachers aged 40-49 years (M=2.693), teachers with master’s degree (M=3.17), teachers with an experience of ˂ 1year (M=2.91), arts teachers (M=2.93), teachers on government payroll (M=2.87) and teachers in rural settings (M=2.88). High job satisfaction was reported among females (M=3.657), diploma holders (M=3.653), teachers on government payroll (M=3.596), teachers with an experience of ˂ 1year (M=3.691), science teachers (M=3.681), teachers aged ˂ 30years (M=3.787) and teachers in urban schools (M=3.62). Self-efficacy was high among teachers with ˂ 1year experience (M=3.497), females (M=3.495), teachers in urban schools (M=3.459), teachers with master’s degree (M=3.454), teachers on government payroll (M=3.358), science teachers (M=3.403) and teachers aged ˃ 50 years (M=3.455). Turnover intentions were high among teachers with master’s degree (M=3.004), teachers aged ˃ 50 years (M=2.801), teachers on PTA payroll (M=2.662), females (M=2.6001), teachers with an experience of ˂ 1 year (M=2.609), arts teachers (M=2.701) and teachers in rural schools (M=2.608). Implications to Theory, Practice and Policy: There is need for development of mentorship programs to help early-career teachers navigate professional challenges to reduce stress and build confidence, enhance job satisfaction so as to mitigate turnover intentions.
Keywords: Stress; Satisfaction; Self-Efficacy; Turnover; Teachers